2012
DOI: 10.1136/ard.2011.153965
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and determinants of aesthetic discomfort in hand osteoarthritis

Abstract: Aesthetic discomfort is a major concern for a significant number of patients with HOA, particularly women, those with a high burden of HOA disease and those with erosive osteoarthritis, and is also associated with depression, anxiety and poor health-related quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
41
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 26 publications
9
41
1
Order By: Relevance
“…In the present study in consecutive patients with HOA, a high prevalence (51%) of EOA was found, which is in accordance with prevalences of EOA in other rheumatology clinics 20. An explanation for this high prevalence could be the source of patients being a rheumatology outpatients clinic.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study in consecutive patients with HOA, a high prevalence (51%) of EOA was found, which is in accordance with prevalences of EOA in other rheumatology clinics 20. An explanation for this high prevalence could be the source of patients being a rheumatology outpatients clinic.…”
Section: Discussionsupporting
confidence: 91%
“…Hodkinson et al have recently shown aesthetic discomfort to be a major concern for more than 30% of patients with HOA, and associated with depression, anxiety and poor QoL. However, in our study, patients who rated many domains as highly important were similar in their pain, function and global assessment compared to patients who endorsed fewer domains.…”
Section: Discussioncontrasting
confidence: 71%
“…Although there have been some outcome measures used in clinical trials, the majority have not taken into consideration the perspectives of patients who have HOA . For instance, aesthetic discomfort is only recently recognized as a major concern affecting a sizable proportion of patients with HOA …”
Section: Introductionmentioning
confidence: 99%
“…Nodal OA occurs more often in women than in men and occurs most often in the dominant hand, suggesting the involvement of mechanical and hormonal factors 40 . Patients with nodal OA frequently have synovitis, osteophytes, cartilage loss, and central and marginal erosions 42 ; aesthetic discomfort is also common 43 . A strong positive association between the presence of nodes and radiographic OA (in particular the occurrence of JSN) supports the notion that a clinical observation of nodes can be taken as an indication of hand OA without the need for radiographic assessment .…”
Section: [H1] Disease Presentation and Burdenmentioning
confidence: 99%